Representações, significados e reflexões: uma análise linguística sobre a experiência docente em um diário reflexivo - Fernandes, Cláudia Regina Ponciano (2009)
Situated in the field of Applied Linguistics, the present study addresses the representations, construction of meaning, and reflective practice of a public school teacher of English in northeastern Brazil. The teacher documents her academic and professional trajectory through a reflective journal (BAILEY, 1990; PEYTON, 1990; MACHADO, 1998, 2007; ZABALZA, 2004; LIBERALI, 1999; BURTON, 2005, and REICHMANN, 2007). The journal is a way to unveil the teacher´s successes, failures, sensations, and perceptions. In this case study, fourteen narratives in the reflective journal constitute the corpus; voice and ´pedagogical truths´ (MOITA LOPES, 2004) surface in these teacher narratives. In this study, I defend the idea that language is used to construe and maintain interpersonal relations, to represent and interpret the world of others and our own, to represent knowledge and to construct meaning (HALLIDAY e MATTHIESSEN, 2004). I also argue that a crucial moment in teacher development is critical reflection on past or current practice, so as to improve future practice (FREIRE, 1996). Based on these assumptions, the main objective of this piece of research is to investigate representations of teacher experience and construction of meaning through written narratives in the journal. The three specific objectives are the following: to describe and to interpret lexico-grammatical choices in selected fragments, from the perspective of the transitivity system (HALLIDAY, 1994); to investigate meaning construction in relation to the academicprofessional context construed in teacher narratives, through other significant linguistic choices; and to examine reflective practice in the journal, focusing on the form of action reconstruction (SMYTH, 1992). Linguistic analysis reveals that teacher discourse represents, reflects and reconstrues academic-professional experience mainly through material and relational Processes, signaling doing, being and becoming, and, furthermore, that there are signs of critical reflection. In sum, as a contribution to the field, this study highlights the importance of the teacher-as-researcher stance, whereby teachers investigate and reflect on language use as social practice in their own academic-professional contexts.